The impact of production potential on the effectiveness of the timber industry ("Journal "U". Economy. Management. Finance.", 2023)
The production potential of an enterprise is a complex of resources placed at its disposal for creative activity. Quantitative characteristics of these resources are usually related to their volume and capacity. For example, the volume of raw materials, the number of jobs or the capacity of equipment. Qualitative characteristics, on the other hand, refer to quality characteristics such as product quality, employee qualifications, or level of maintenance. Integration of these resources may be necessary to ensure efficiency and productivity. For example, the use of automated production management systems that combine data from equipment, raw materials, workers and other resources can reduce production management costs and improve the quality of products. One of the most important tasks in this context is to optimize the structure of the enterprise, take into account the resource potential and make decisions based on the analysis of the competition.
Keywords: potential; production potential; impact; effectiveness; performance management; efficiency; methodological approaches; strategy; development; resources; market economy; timber enterprise